Pilates Reducing Falls Risk Factors in Healthy Older Adults: A Systematic Review and Meta-Analysis - da Silva, Larissa Donatoni; Shiel, Agnes; McIntosh, Caroline (Frontiers in Medicine, 2021)
Background: This systematic review and meta-analysis aimed to synthesise the evidence and research findings from randomised controlled trials of Pilates intervention in comparison to control groups and other forms of exercise. Methods: The following electronic databases, were searched up to October 2020; EMBASE, Scopus, Google Scholar, MEDLINE (Ovid), Science Direct, Cochrane and CINAHL. The recommendations of the Preferred Reporting Items of Systematic Reviews and Meta-Analyses were followed. Results: Pilates showed an effect in mediolateral directions in comparison to control groups (MD = -1.77, 95% CI, -2.84 to -0.70, p = 0.001, heterogeneity: I² = 3%), mobility (MD = 9.23, 95% CI, 5.74 to 12.73, p < 0.00001, heterogeneity: I² = 75%) and fear of falling (MD = -8.61, 95% CI, -10.16 to -7.07, p < 0.00001, heterogeneity: I² = 88%). In relation to other exercises group, Pilates showed positive effects in functional mobility (MD= -1.21, 95% CI, -2.30 to -0.11, p = 0.03, heterogeneity: I² = 80%), mobility (MD = 3.25, 95% CI, 1.46 to 5.04, p < 0.0004, heterogeneity: I² = 0%). No evidence of an improvement was found between the groups for dynamic gait index (MD = 2.26, 95% CI, -0.05 to 4.56, p = 0.06, heterogeneity: I² = 86%), anteroposterior directions of balance (MD = -1.58, 95% CI, -3.74 to -0.59, p = 0.15, heterogeneity: I² = 51%) and functional mobility when compared to control groups (no exercise) (MD = -1.24, 95% CI, -2.48 to -0.00, p = 0.05, heterogeneity: I² = 87%). Conclusion: Pilates may be effective in decreasing the risk of falls in older adults; Pilates intervention was found to improve functional mobility, mobility, gait, fear of falling and postural stability. There is an absence of quality evidence in regards to the impact of Pilates on reducing falls and further high quality RCTs are needed.